A new vision of mobility guidance to foster collaborative multimodal decision making. - Coogan, Matthew; Meyer, Michael; Casgar, Christina; National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program; TransManagement, Inc. (Washington, D.C. Transportation Research Board, National Research Council, 2004)
This digest summarizes the results of Phase I of a cooperative research effort jointly funded by TCRP Project H-29 and NCHRP Project 8-45 ... This digest was written by a TransManagement, Inc. team, including Matthew Coogan, Michael Meyer, and Christina Casgar.
Caption title.
January 2004.
Keywords: Transportation -- Planning -- Decision making; intermodal transportation